1996
DOI: 10.1046/j.1365-2141.1996.5081049.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased L‐selectin expression in CD34‐positive cells from patients with chronic myelocytic leukaemia

Abstract: Abnormal adhesive interaction between bone marrow stroma and progenitors, one of the causes of unregulated proliferation in chronic myelocytic leukaemia (CML), may be caused by some alterations in adhesion molecules on CML progenitors. We investigated the expression of adhesion molecules (CD44, VLA-5, VLA-4, LFA-1, ICAM-1, L-selectin and c-kit) on bone marrow CD34++ cells from 16 CML patients by three-colour flow cytometry. The mean percentage of cells expressing L-selectin in the CD34++CD38+(or)++ fraction fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 19 publications
(21 reference statements)
1
14
0
Order By: Relevance
“…[31][32][33][34][35][36][37] Decreased mRNA levels for L-selectin in p210 UCB and early CP CML CD34 þ cells is consistent with published reports demonstrating decreased expression of L-selectin on BM CD34 þ cells derived from CML patients. [38][39][40] We observed populations of CD34 þ cells with higher and lower levels of L-selectin protein expression in primary cells as well as in the UCB transduction model possibly based on subpopulations. Hence, it is possible that the decreased levels of ICAM1 and L-selectin in CML samples is due to skewing of the population away from the population expressing higher numbers of these adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37] Decreased mRNA levels for L-selectin in p210 UCB and early CP CML CD34 þ cells is consistent with published reports demonstrating decreased expression of L-selectin on BM CD34 þ cells derived from CML patients. [38][39][40] We observed populations of CD34 þ cells with higher and lower levels of L-selectin protein expression in primary cells as well as in the UCB transduction model possibly based on subpopulations. Hence, it is possible that the decreased levels of ICAM1 and L-selectin in CML samples is due to skewing of the population away from the population expressing higher numbers of these adhesion molecules.…”
Section: Discussionmentioning
confidence: 99%
“…By comparing patterns of antigen expression on a given cell population with the patterns identified on normal cells of that type, one potentially can identify abnormalities that, if sufficiently great, may substitute for clonality studies in identifying malignancy. A small number of studies during the past decade have reported abnormalities of one or a few myeloid antigens in CML, including decreased CD16, 4-6 decreased CD32, 5 decreased L-selectin expression on CD34+ cells, 7 aberrant expression of CD56 on blasts and myeloid cells, 8,9 and aberrant expression of lymphoid antigens such as CD2, CD5, and CD7 on the blasts in CML blast crisis. 10 Reported flow cytometric abnormalities among the NCMPDs have included the Particularly useful combinations of antibodies were those that identified antigens expressed over a wide range of intensities in the population of interest.…”
mentioning
confidence: 99%
“…All these reports lead to the conclusion that the abnormal expression of antigens is not a mere surface abnormality but is related to the intrinsic process generating myelodysplasia. Moving from these acquisitions, we have considered that, if MDS arises from a progressive genetic damage within the haematopoietic stem cell compartment (12,(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), it is also conceivable that other extrinsic or intrinsic mechanisms may contribute to the biology of disease and progression toward sAML. Ratio >1 Ratio <1 P = 0.002 64% 11% Figure 4 The value of L-selectin ⁄ ICAM1 ratio and the risk of disease progression.…”
Section: Discussionmentioning
confidence: 99%